No evidence for adaptation to local rhizobial mutualists in the legume Medicago lupulina. Issue 12 (10th May 2017) - Harrison, Tia L.; Wood, Corlett W.; Borges, Isabela L.; Stinchcombe, John R.
Abstract: Local adaptation is a common but not ubiquitous feature of species interactions, and understanding the circumstances under which it evolves illuminates the factors that influence adaptive population divergence. Antagonistic species interactions dominate the local adaptation literature relative to mutualistic ones, preventing an overall assessment of adaptation within interspecific interactions. Here, we tested whether the legume Medicago lupulina is adapted to the locally abundant species of mutualistic nitrogen‐fixing rhizobial bacteria that vary in frequency across its eastern North American range. We reciprocally inoculated northern and southern M. lupulina genotypes with the northern ( Ensifer medicae ) or southern bacterium ( E. meliloti ) in a greenhouse experiment. Despite producing different numbers of root nodules (the structures in which the plants house the bacteria), neither northern nor southern plants produced more seeds, flowered earlier, or were more likely to flower when inoculated with their local rhizobia. We then used a pre‐existing dataset to perform a genome scan for loci that showed elevated differentiation between field‐collected plants that hosted different bacteria. None of the loci we identified belonged to the well‐characterized suite of legume–rhizobia symbiosis genes, suggesting that the rhizobia do not drive genetic divergence between M. lupulina populations. Our results demonstrate that symbiont local adaptation has not evolved in this mutualism despite large‐scale geographic variation in the identity of the interacting species. Abstract : Tests of local adaptation between interacting species are biased toward antagonisms. Here, we tested for symbiont local adaptation in the mutualism between the legume Medicago lupulina and two species of nitrogen‐fixing bacteria. Despite a large‐scale cline in the frequency of the two bacteria, we found no evidence that M. lupulina is adapted to its local bacteria.